(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
In the first and at the beginning of the second part of this work the methodology for creation of 2D colourful diagrams has been described as thematically-oriented sequence of the used procedures of MS Excel 2010. In this part of the work the methodology has been applied for the preparation of 2D colourful diagrams of temperature distribution in the longitudinal sections of a frozen oak log during its defrosting. The methodology can be used for the preparation of various 2D diagrams for the change of temperature, moisture, and other fields in the volume of different materials in the cases when the diagrams are created using extensive numerical results from models, adequately describing the studied processes.